Pengaruh Proses Produksi terhadap Kualitas Produk yang Dimoderasi oleh Pelatihan (Kasus pada Produsen Sepatu di Kabupaten Tangerang) - Kasfia, Selkia Royyan; Moh. Mukhsin; Satyanegara, Diqbal (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The conducted research focuses on examining the impact of production processes affecting product quality, with training considered as a reinforcing element. This study takes the case of CV. Kitos Jaya, a shoe factory located in the Tangerang Regency area, where there has been an issue of declining product quality levels produced by the company. This study implements an associative method guided by a quantitative approach. Data collection involved 120 respondents who are workers, with sample selection using saturated sampling technique. For data testing, this research utilizes Structural Equation Modeling (SEM) analysis processed using Smart-PLS software version 4.0.9.9. Based on the tests conducted, it is proven that the production process generates a significant positive impact on product quality. Similarly, training demonstrates a significant influence on improving product quality. However, when tested as a moderating variable, training does not demonstrate the ability to strengthen the relationship between the production process and product quality. This finding underlines an important recommendation for management: although production processes and training each play crucial roles in improving product quality, these two aspects should not be combined as a moderation model.